IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA GURU DAN KARYAWAN DI SDN MAGETAN 1 - Nanang Mulyanto (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2022)
Nanang Mulyanto Sekolah Tinggi Agama Islam Ma’arif Magetan kopral.nangmol@gmail.com Abstract What is the Transformational Leadership Style of the Head of SDN Magetan 1? How are the teachers and employees of SDN Magetan 1 performing? How is the implementation of the transformational leadership of the Head of SDN Magetan 1 in improving the performance of teachers and employees? In this regard, in this descriptive qualitative research using the observation method, namely receiving all data obtained from observations and systematic records of the phenomena being investigated, the interview method is receiving data by means of communication with data sources directly, and documentation methods, namely taking data obtained through documents. Meanwhile, in data analysis, researchers use the Trianggulation technique, namely researchers dig up as much data as possible from the research subjects then the data obtained is dug back to other related respondents, so that the data that has been obtained is really valid. Using trianggulation analysis techniques, the results of this study show that the implementation of leadership of the head of SDN Magetan 1 in improving the performance of teachers and employees uses transformational leadership patterns. Namely a leader who has a special character, namely: (1). idealized influence, behavior that produces respect (respect) and self-confidence (trust) from the person he leads. (2). inspirational motivation, reflected in behavior that always provides challenges for the work done by staff and pays attention to the meaning of work for staff. (3). intellectual stimulation, that is, leaders who make innovations. (4). Individualized consideration, the leader reflects on himself as a person who is attentive in listening to and following up on complaints, ideas, expectations, and all inputs provided by staff. This conclusion can be proven through the results of interviews with the principal and related respondents, namely teachers and school employees. Keywords : Implementation of transformational leadership of principals, Performance of Teachers and Employees.